IACS/IAPSO/OCEAN:ICE joint session at IUGG OCEAN:ICE interactions – Ice sheet impacts on ocean circulation and climate feedbacks (MS26) ... - Meijers, Andrew; Mottram, Ruth (Zenodo, 2023)
This is the report of the Milestone MS26 on the IACS/IAPSO/OCEAN:ICE joint session at IUGG OCEAN:ICE interactions – Ice sheet impacts on ocean circulation and climate feedbacks JP03/JP04 Breakout Discussion Session. The session was organised on 14 July 2023 at IUGG in Berlin. ...